Development of pharmacist's counselling guide, flipchart and booklet for patients with hypertension - Ocsan, Prince Mark F.; Uy, Holijah T.
Hypertension remains to be a major health problem both in the world and here in the Philippines. Globally, it contributes to approximately 50% of deaths caused by cardiovascular diseases. In recent studies, it has shown that medication alone is not able to control the prevalence of hypertension as it still remains troublesome in 73% of adults who are already taking anti-hypertensive drugs. This highlights now the role of health professionals, such as pharmacist, to provide patients with interventions like counselling that would help them in obtaining the maximum benefit from the medications that they take. This study aimed to develop counselling tool that would aid in counselling patients with hypertension. Specifically, it intends to determine patient counselling information that are to be incorporated in the pharmacist's guide, flipchart and patient's booklet, identify common inquiries that pharmacists encounter in counselling patients with hypertrension, and assess the effect of the counselling tool on the knowledge of patients with hypertension. It consists of two phases, Phase One: Development of Counselling Tool and Phase Two: Pre-Test and Post-Test Evaluation of the Tool. Results of the study have shown an improvement in the mean scores of patients from 7.5/10 to 8.67/10 after being counselled with the developed tool, therefore highly indicating a positive effect of the tool in the knowledge of hypertensive patients about hypertension and its management.
Thesis (BS in Pharmacy) University of the Philippines Manila
Keywords: Pharmaceutical Services; Hypertension